Technology assessment and requirements analysis: a process to facilitate decision making in picture archiving and communications system implementation...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: performance improvement in radiology.' Houston TX, May 6-9, 1999 - Radvany MG; Chacko AK; Richardson RR Jr.; Grazdan GW (Journal of Digital Imaging)
In a time of decreasing resources, managers need a tool to manage their resources effectively, support clinical requirements, and replace aging equipment in order to ensure adequate clinical care. To do this successfully, one must be able to perform technology assessment and capital equipment asset management. The lack of a commercial system that adequately performed technology needs assessment and addressed the unique needs of the military led to the development of an in-house Technology Assessment and Requirements Analysis (TARA) program. The TARA is a tool that provides an unbiased review of clinical operations and the resulting capital equipment requirements for military hospitals. The TARA report allows for the development of acquisition strategies for new equipment, enhances personnel management, and improves and streamlines clinical operations and processes. Copyright (c) 1999 by W.B. Saunders Company